2021
DOI: 10.1099/mic.0.001050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the antimicrobial activity of the macrophage metabolite itaconate

Abstract: The production of itaconate by macrophages was only discovered in 2011. An increasing number of studies have since revealed essential biological functions for this small molecule, ranging from antimicrobial to immunomodulator. The antibacterial role of itaconate has however been questioned because the estimated concentration of itaconate in macrophages (low-millimolar) is lower than the minimum inhibitory concentration (MIC) of itaconate reported for several bacterial strains (low-to-mid-millimolar). We note t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
1
9
2
Order By: Relevance
“…However, the microbicidal activity of itaconate is most likely dependent on pH, since neutralization made it less efficient in inhibiting M. avium growth in culture. This was also recently suggested by others ( 42 , 43 ). There are also conflicting reports with regard to the membrane permeability of itaconate, and several derivatives have been made to facilitate cellular uptake ( 30 , 60 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the microbicidal activity of itaconate is most likely dependent on pH, since neutralization made it less efficient in inhibiting M. avium growth in culture. This was also recently suggested by others ( 42 , 43 ). There are also conflicting reports with regard to the membrane permeability of itaconate, and several derivatives have been made to facilitate cellular uptake ( 30 , 60 ).…”
Section: Discussionsupporting
confidence: 86%
“…6E ). It was recently shown that millimolar concentrations of itaconate acidify the medium but also that the bactericidal activity of itaconate is enhanced under acidic conditions, such as in the phagolysosome ( 42 , 43 ). In line with this, the neutralization of itaconate using NaOH reduced the growth-inhibitory effect of M. avium in liquid culture ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ACOD1-mediated ITA generation appears to be required for curbing C. burnetii growth in macrophages. Since the first report of inhibition of M. tuberculosis by ITA (Michelucci et al, 2013), a similar effect has been shown for other intracellular bacteria, including M. avium (Gidon et al, 2021), L. pneumophila (Naujoks et al, 2016), Salmonella (S.) typhimurium (Chen et al, 2020), Brucella melitensis (Demars et al, 2021;Lacey et al, 2021) and F. tularensis (Jessop et al, 2020), but also for the extracellular bacteria Escherichia (E.) coli (Duncan et al, 2021) and Staphylococcus (S.) aureus (Singh et al, 2021). Remarkably, the ITA concentrations that we found to be required for inhibition of C. burnetii growth in macrophages or axenic cultures (0.6 -2.5 mM), were lower than those documented for the above-mentioned pathogens (> 5 mM).…”
Section: Discussionmentioning
confidence: 55%
“…For other bacteria, the mechanism of growth inhibition by ITA is unknown to date. Given the acidic conditions in the phagolysosome, the recent demonstration of synergy between ITA and low pH for blocking replication of E. coli and S. typhimurium (Duncan et al, 2021) is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ACOD1‐mediated ITA generation appears to be required for curbing C. burnetii growth in macrophages. Since the first report of inhibition of M. tuberculosis by ITA (Michelucci et al , 2013 ), a similar effect has been shown for other intracellular bacteria, including M. avium (Gidon et al , 2021 ), L. pneumophila (Naujoks et al , 2016 ), Salmonella (S.) typhimurium (Chen et al , 2020 ), Brucella melitensis (Demars et al , 2021 ; Lacey et al , 2021 ) and F. tularensis (Jessop et al , 2020 ), but also for the extracellular bacteria Escherichia (E.) coli (Duncan et al , 2021 ) and Staphylococcus (S.) aureus (Singh et al , 2021 ). Remarkably, the ITA concentrations that we found to be required for inhibition of C. burnetii growth in macrophages or axenic cultures (0.6–2.5 mM), were lower than those documented for the above‐mentioned pathogens (>5 mM).…”
Section: Discussionmentioning
confidence: 99%